Transparent 3-Layered Bacterial Nanocellulose as a Multicompartment and Biomimetic Scaffold for Co-Culturing Cells - Karla Pollyanna Vieira de Oliveira; Michael Yilma Yitayew; Ana Paula Almeida Bastos; Stefanie Cristine Nied Mandrik; Luismar Marques Porto; Maryam Tabrizian (Journal of Functional Biomaterials, 2025)
Three-dimensional (3D) cell culture models are widely used to provide a more physiologically relevant microenvironment in which to host and study desired cell types. These models vary in complexity and cost, ranging from simple and inexpensive to highly sophisticated and costly systems. In this study, we introduce a novel translucent multi-compartmentalized stacked multilayered nanocellulose scaffold and describe its fabrication, characterization, and potential application for co-culturing multiple cell types. The scaffold consists of bacterial nanocellulose (BNC) layers separated by interlayers of a lower density of nanocellulose fibers. Using this system, we co-cultured the MDA-MB-231 cell line with two tumor-associated cell types, namely BC-CAFs and M2 macrophages, to simulate the tumor microenvironment (TME). Cells remained viable and metabolically active for up to 15 days. Confocal microscopy showed no signs of cell invasion. However, BC-CAFs and MDA-MB-231 cells were frequently observed within the same layer. The expression of breast cancer-related genes was analyzed to assess the downstream functionality of the cells. We found that the E-cadherin expression was 20% lower in cancer cells co-cultured in the multi-compartmentalized scaffold than in those cultured in 2D plates. Since E-cadherin plays a critical role in preventing the initial dissociation of epithelial cells from the primary tumor mass and is often downregulated in the tumor microenvironment in vivo, this finding suggests that our scaffold more effectively recapitulates the complexity of a tumor microenvironment.